Efficacy, persistence, ground deposition, and human exposure of polymer-encapsulated lindane and chlorpyrifos used for control of the southern pine beetle - Berisford, C.W.; Dalusky, M.J.; Bush, P.B.; Taylor Jr., J.W.; Berisford, Y.C. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1991)
Formulations of lindane and chlorpyrifos were evaluated to determine if polymer encapsulation extended the duration of southern pine beetle (Dendroctonusfrontalis) control, reduced ground deposition, increased persistence on bark or reduced potential human exposure relative to emulsifiable concentrate formulations. Encapsulation did not extend efficacy or reduce ground deposition of either insecticide when compared with the standard emulsifiable formulations. Encapsulation extended residue persistence of chlorpyrifos on bark, but not of lindane. The potential risk of human exposure to bark which was still wet with chlorpyrifos was increased 2.2 times by encapsulation, whereas, similar exposure to lindane was unaffected by encapsulation. After the insecticides had dried on the bark, the encapsulated formulations reduced risk to lindane by approximately 90% and by 83 % for chlorpyrifos.